Penerapan manajemen risiko operasional pada mobile banking syariah - Anggraini, Jesika Devi Mufita (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has encouraged Islamic banks to provide mobile banking services as a fast, practical, and efficient transaction platform. However, behind this convenience lie various operational risks arising from human error, system failures, weak internal processes, and external threats such as cybercrime. This study aims to analyze the implementation of operational risk management in Islamic mobile banking and its relationship with Sharia compliance in maintaining customer trust. The research uses a descriptive qualitative approach through a literature review of relevant sources. The findings show that operational risk management is carried out through the stages of risk identification, measurement, monitoring, and control on a continuous basis. The implementation of digital security systems, strengthening internal controls, and improving human resource competencies are the main strategies to minimize risks. In addition, Sharia compliance plays an important role in ensuring that all services and transactions are in accordance with Islamic principles, thereby enhancing reputation and customer confidence. The integration of operational risk management and Sharia compliance is proven to be an essential factor in creating secure, reliable, and sustainable mobile banking services. Therefore, Islamic banks need to continuously innovate and strengthen supervisory systems to address the dynamic risks of the digital era.